New Commands to Improve the Monitor for the ELWE Microcomputer (Journal of the College of Education for Women, 2019)
The base of the ELWE MPF-1 microcomputer is the Z80 microprocessor. The Z80 programs are written in assembly language. The main advantage of assembly language is that: it is much faster to code and the mnemonics makes it easier for the user to remember the instruction. The purpose of this paper is to improve the monitor process for didactic microcomputer ELWE MPF-1 by appending new powerful commands (MOVE, FILL, SEARCH and COMPARE) to the existing monitor to make it more useful and flexible. 8085 assembly language is used to execute this program. The letters used for abbreviation: M for MOVE, F for FILL, S for SEARCH and C for COMPARE.